External load of professional female soccer players in the competitive microcycle: Influence of playing position and contextual variables - Sánchez-Abselam, O.; González-Fernández, F. T.; Castillo-Rodríguez, A.; Onetti-Onetti, W. (The Journal of Strength and Conditioning Research, 2026)
Women's soccer has experienced substantial growth in recent years, accompanied by increased scientific interest in performance-related variables. This study aimed to analyze the external load across competitive microcycles in a professional women's soccer team and to examine the influence of playing position and contextual factors (match location, outcome, and opponent quality) on physical demands. Eighteen professional players (age: 24.5 ± 5.6 years; body mass: 58.8 ± 14.8 kg; height: 165 ± 5.7 cm) from a Spanish second-division team were monitored across 13 microcycles using 10 Hz Global Positioning System devices. Players were categorized into 5 positions: central defenders, external defenders, midfielders, wingers, and forwards. Significant differences were observed across microcycle days (p < 0.001), with match day (MD) presenting the highest external load values, and MD-1 the lowest. Playing position significantly affected explosive distance, high-speed running, and high metabolic load distance (p < 0.001), with forwards showing the highest values and central defenders the lowest. In addition, greater physical demands were recorded when competing against lower-ranked opponents. These findings provide relevant insights for physical performance staff, highlighting the importance of adjusting training loads based on both positional profiles and contextual factors to optimize performance and recovery strategies in elite women's soccer.